Transgression of the Concept of Public-Private (Global Journal of Human-Social Science, 2015)
In this era of individualism almost everyone is concerned about maintaining the privacy, but it becomes too confusing as the core concept of public and private can no more be described in a straight and easy way. Both of these issues get different dimensions which actually transgress the characteristics of being "Public" or being "Private". Even the concerns of people about privacy and concealing or sharing their private matters or experiences are also changed. This paper deals with present ideas regarding these complicated issues of public and private, how these changes are occurred, which trend works behind this change and also the existing psychology of the modern people regarding the conception of privacy and public matters. Earlier, while people kept diary to reflect their dreams, pain and pleasure, but now the technocrat people share almost every thinking firstly in the "What's on your mind" box in Face book. It becomes so normal to share the mind with lots of people. In this capitalist and corporate world human being are no more treated as human being rather they are treated as commodity. Privacy and livelihood of individuals become victims of dominant corporate culture. Their experience, life style, emotion everything become the products for selling.
Keywords: individualism; public; private; transgression; gaze; panopticon; social media commoditization